Infectious diseases during pregnancy in Brazil: seroprevalence and risk factors - Costa, Galileu Barbosa; de Oliveira, Mário Cézar; Gadelha, Sandra Rocha; Albuquerque, George Rego; Teixeira, Marcel; Raiol, Monica Regina da Silva; Sousa, Sandra Mara Bispo; Marin, Lauro Juliano (The Journal of Infection in Developing Countries, 2018)
Introduction: Vertically transmitted infections are caused by a diversity of pathogenic microorganisms. Pregnant women are routinely screened to evaluate the risks and reduce the burden of disorders in their unborn children. We assessed the prevalence and possible risk factors for Cytomegalovirus (CMV), Rubella, Human T lymphotropic virus (HTLV), and Toxoplasma gondii in pregnant women from the South region of Bahia State, Brazil. Methodology: Serum samples were obtained from 726 pregnant women aged between 13 and 44 years, with a median age of 24 years. ELISA assays were used to detect CMV, Rubella, HTLV and T. gondii IgG and IgM antibodies. Results: The prevalence rates of IgG antibodies found were 95.2% for CMV, 97.0% for Rubella, and 72.3% for T. gondii. Furthermore, the prevalence of HTLV-1/2 was 1.2%. IgM antibodies were reactive only for CMV (0.8%) and T. gondii (3.7%). Variables independently associated with the detection of anti-T. gondii IgG antibodies were white self-reported race/ethnicity (Odds Ratio [OR] 2.26, 95% CI 1.26–4.06, P = 0.006), wage income (OR 0.55, 95% CI 0.35–0.88, P = 0.013), and history of previous pregnancy (OR 1.60, 95% CI 1.02–2.50, P = 0.038). Conclusions: This study highlights the importance of monitoring for infectious diseases during pregnancy and initiation of early interventions to reduce the burden of fetal losses and other important infant sequelae attributable to congenital infections.